Interhemispheric radio-astrochronological calibration of the time scales from the Andean and the Tethyan areas in the Valanginian-Hauterivian (Early Cretaceous). - Tunik, Maisa A. (2019)
Fil: Tunik, Maisa A. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro; Argentina